2012
DOI: 10.1088/1742-6596/362/1/012008
|View full text |Cite
|
Sign up to set email alerts
|

Compressibility and rarefaction effects on entropy and entropy generation in micro/nano Couette flow using DSMC

Abstract: Abstract. In the present work, compressible flow of argon gas in the famous problem of Couette flow in micro/nano-scale is considered and numerically analyzed using the direct simulation Monte Carlo (DSMC) method. The effects of compressibility and rarefaction on entropy and entropy generation in terms of viscous dissipation and thermal diffusion are studied in a wide range of Mach and Knudsen numbers and the observed physics are discussed. In this regard, we computed entropy by using its kinetic theory formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…The influence of relevant parameters on the local Nusselt number distribution is shown in Figure 5 . Ejtehadi [ 64 ] analyzed the influence of compressibility and rarefaction on micro/nanoscale Couette flow from the perspective of entropy generation. Research showed that the increase of Mach number leads to non-uniform entropy profiles near the central region of the channel.…”
Section: Flow and Heat Transfer Mechanism Of Single-phase Fluid Under...mentioning
confidence: 99%
“…The influence of relevant parameters on the local Nusselt number distribution is shown in Figure 5 . Ejtehadi [ 64 ] analyzed the influence of compressibility and rarefaction on micro/nanoscale Couette flow from the perspective of entropy generation. Research showed that the increase of Mach number leads to non-uniform entropy profiles near the central region of the channel.…”
Section: Flow and Heat Transfer Mechanism Of Single-phase Fluid Under...mentioning
confidence: 99%
“…Measuring the roughness of nano¯brous structures by AFM has been suggested by some researchers. [10][11][12][13][14][15][16][17][18] Baltsavias compared two di®erent approaches of roughness measurement. The results show that the indirect method is more practical and useful for calculation of standard surface pro¯le measurement, compared with the stylus pro¯lometer for characterization of a surface topography.…”
Section: Introductionmentioning
confidence: 99%
“…The open literature shows a very small number of papers that deal with entropy generation related problems in the field of microfluidics. Ejtehadi et al (2012) numerically analyzed compressibility and rarefaction effects on entropy generation in a micro/nano Couette flow using the direct simulation Monte Carlo (DSMC) method. Under more general conditions Ibanez and Cuevas (2010) analyzed, the thermal behavior of viscous fluid flow in a parallel wall microchannel subjected to electromagnetic interaction.…”
Section: Introductionmentioning
confidence: 99%